Long‐term survival in horses with strangulating obstruction of the small intestine managed without resection. (7th January 2014) - Freeman, D. E.; Schaeffer, D. J.; Cleary, O. B.
Summary: Reasons for performing study: Although many studies have described results after small intestinal resection and anastomosis in horses, few have described the outcome in horses with strangulating lesions managed without resection. Objectives: To examine short‐ and long‐term recoveries in horses with strangulated small intestine that was judged to be viable during surgery and not resected. Study design: Retrospective analysis of case records. Methods: Data were reviewed from all cases (35 horses) with colic caused by small intestinal strangulation that underwent surgery between 1996 and 2011 at 2 university hospitals and that were managed without resection by 2 surgeons who used a clinical grading system to assess intestinal viability. Kaplan–Meier analyses were used to examine long‐term survival. Results: Survival to discharge from the hospital was 100%, and post operative complications developed in 11 horses (31%). Three horses (8.6%) required repeat coeliotomy because of persistent pain with or without reflux, and they responded favourably to decompression of distended intestine. Ten horses died after discharge, and 12 were still alive at follow‐up from 20 to 192 months after surgery. Information was available on 13 horses after discharge, but these were eventually lost to follow‐up. Kaplan–Meier analyses yielded a median survival probability of 120 months. Conclusions: A subjective method of assessing small intestinal viability in strangulated small intestine in horses, as used in this study, could reduce the need for resection and anastomosis, with the associated complications and costs. Also, the favourable post operative course in these horses provides strong evidence that early referral could avoid the need for resection and improve survival. The numbers of horses with the most severe changes that were not resected were too small to allow a conclusion that such segments should be left in place, and additional criteria might be needed to guide that decision in such cases.